APAKAH HASIL BELAJAR EKONOMI DIPENGARUHI OLEH MOTIVASI BELAJAR DAN KEAKTIFAN BELAJAR? - Dwi Candra Fahrul Aditya Wahyu Hidayat; Putri Ulfa Kamalia, Putri Ulfa Kamalia (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Education aims to educate students to become human beings who are knowledgeable, creative, independent, capable, noble and responsible, these goals can be achieved with learning motivation and active learning in learning so that the learning outcomes obtained are good, especially in economic subjects. The purpose of this study was to determine 1) the partial effect of learning motivation variables on economic learning outcomes, 2) the effect of learning activities on economic learning outcomes, 3) the simultaneous influence of learning motivation variables and learning activities on economic learning outcomes in class X IPS SMAN 1 Cerme. The sampling method used is purposive sampling resulting in a sample of 86 students. This study uses primary data obtained from questionnaires. The results of this study indicate that there is a partially significant positive effect between learning motivation on economic learning outcomes with a sig value of 0.021 <0.05 and t count 2.353 > t table 1.98896, and there is a significant positive effect of learning activity variables on economic learning outcomes with sig value 0.019 < 0.05 and t count 2.399 > t table 1.98896. Also simultaneously there is a significant positive effect between learning motivation and learning activities on economic learning outcomes with a sig value of 0.000 <0.05 and a calculated F value of 27.079 > F table 3.11 and with an Adjusted R-squared value of 0.380 the contribution of the independent variables is 38%. .